A preliminary investigation of the toxic effects of Benzylpenicilloic acid. (January 2018) - Cui, Cheng; Lu, Huijun; Hui, Qi; Lu, Shiying; Liu, Yan; Ahmad, Waqas; Wang, Yang; Hu, Pan; Liu, Xilin; Cai, Yan; Liu, Lingjiu; Zhang, Xiang; et al.
Abstract: Benzylpenicilloic acid (BPNLA) is a major cleavage product of benzylpenicillin G (BP) generated after heating treatment. It is found in animal derived products from the unstable residual penicillin. Previous studies have only reported the allergic reaction caused by BPNLA, but not described its toxicity. In this study, the toxicity of BPNLA was evaluated to report the potential public health risk posed by animal derived products using in vivo and in vitro models, including the acute toxicity assays, cytotoxicity assays, apoptosis assays and cell cycle progression assay. The LD50 value for BPNLA was 8.48 g/kg [bw] intraperitoneally. BPNLA showed cytotoxicity and inhibition of cell proliferation on SK-N-SH cells, MRC-5 cells and GC-1 cells. Further, Annexin-v/PI staining and Hoechst 33342 staining showed increased cell apoptosis and nucleus morphological changes with toxic levels of BPNLA. BPNLA arrested cells in G1 phase and reduced cells population in S phase in a dose-dependent manner. This work suggests that BPNLA might be a potential toxic agent and might have public health significance. However, the toxic concentrations of BPNLA are relatively high compared to levels that would result from the degradation of antibiotics residues in meat from animals that have received a therapeutic dose of benzylpenicillin. Graphical abstract: Highlights: High concentrations of BPNLA induce acute toxicity in vivo with a LD50 of 8.48 g/kg. BPNLA induces cytotoxicity in different human and murine in vitro cell lines via the inhibition of both cell viability and proliferation. BPNLA toxicity leads to the activation of the apoptosis pathways. BPNLA disrupts cell cycle by inducing G1 phase arrest and S phase reduction. Cell lines derived from the reproductive system appear to be more sensitive in response to BPNLA.